A study of vitamin D levels and associated deficiency in pregnancy and its effect on maternal and fetal outcome - Dave, Anupama; Verma, Monica; Jain, Neelam; Dave, Atisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: From conception the embryo is dependent on the mother for all nutritional requirements until birth. Vitamin D deficiencies have adverse effect on pregnancy outcome result in poor growth, prematurity, NTD, even congenital anomalies. The aim and objectives of the study was to assess the prevalence of deficiencies among pregnant woman attending M.Y. Hospital and assess the correlation with the pregnancy complications. Methods: Total 110 patients were studied for vitamin d levels and associated obstetrical complications and risk factors over a period of six months. 53 pregnant women were found to be deficient with vitamin D. Results: 53 pregnant women out of total of 110 were deficient in vitamin D levels. Maximum patients belonged to group (21-30yr) of age. Vitamin D deficiency was more in housewives (65.3%) and in urban(86.8%). Low birth weight<2.5kg were born 50(45.5%) and 2 IUD. 2 were diagnosed NTD in USG reports. 80% low birth weight babies were born in vitamin D deficient women. Conclusions: Our study fails to show a causal relation between low vitamin D level and adverse maternal and fetal outcome in terms of preeclampsia, cesarean delivery, oligo and diabetes. There was a relation between vitamin D deficiency and low birth weight babies.